Global research trends and prospects on the first-generation college students from 2002 to 2022: a bibliometric analysis via CiteSpace - Fei, Li; Kang, Xizhen; Sun, Weiming; Hu, Boxiang (Frontiers in Psychology, 2023)
Objectives To review literature related to first-generation college students, the paper aims to outline the research direction, identify prominent research topics and frontiers, report on current research trends, and offer valuable insights and fresh perspectives for future advancements in the field, utilizing CiteSpace. Methods CiteSpace is a citation visualization software designed to analyze the scholarly literature and uncover potential knowledge within it. This study retrieved articles related to first-generation college students from 2002 to 2022 from Web of Science Core Collection database. After collecting the data, CiteSpace V.6.1.R3 (64-bit) was used to perform analyses on various aspects, including annual publication output, top cited journals, country and institutional affiliations, prominent authors, cited references, and keywords. The data was visualized using tools such as knowledge maps, collaborative network analysis, cluster analysis, and strongest citation burst analysis. Results We obtained a total of 471 articles on first-generation college students. The number of publications annually is increasing, and the number of publications generally shows an upward trend, especially in 2017–2021 with a sharp growth. The United States has the most articles on this topic (395 articles), and it is also the most authoritative and influential country (with a centrality of 0.93). Followed by South Africa (14 articles) and Germany (14 articles), The top 10 cited journals and institutions are predominantly from the United States. When analyzing the top cited references and authors, the research consistently highlights the academic achievement and engagement of first-generation college students. Conclusion This study analyzed the current situation of first-generation college students field via CiteSpace, then identify the research hotspots and frontiers on first-generation college students. Current global trends in first-generation college students researches and the growing public awareness of academic performance and equality suggest that first-generation college students researches will grow in popularity with further breakthroughs.